GOVERNMENT LEGAL ACT COMPARISON BETWEEN INDONESIA AND SOUTH KOREA IN HANDLING COVID-19 PANDEMIC - Isma Novalia Firdha Susanto; Bayu Aji Satria; Sholahuddin Al-Fatih (Universitas Muhammadiyah Tangerang, 2021)
Coronavirus Disease of 2019 (COVID-19) with the official name of SARS-CoV-2 has been a serious emerging alert for countries around the world, which makes it a global outbreak of respiratory illness caused by a novel (new) coronavirus. Some countries did a remarkable job on flatten their COVID-19 case rate curve, the finest world reputation in handling this pandemic is given to the Republic of Korea or more known as South Korea which has amazed other world leaders wondering how Moon Jae-in, current President of South Korea, has successfully implied effective and accurate strategies in handling this world outbreak in South Korea. Asides from South Korea succeed, there are some countries who are fall way behind such as the Republic of Indonesia who is currently concerning not only in the medical sector, but the emerging economic sector is severely impacted which leaves us a solicitous feeling towards the future of our nation. In this case, a comparative study is needed to reflect on what has not yet done right. This paper discusses what sort of precise policy reconstructions should be adapted by the Indonesian government from the South Korean government’s effective strategy accuracy in handling COVID-19.